THE EFFECT OF CAPITAL STRUCTURE AND CORPORATE INCOME TAX PAYABLE ON PROFIT MANAGEMENT IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2022-2024 - M. Tarmizi; Yuli Maylena; Sujeni, Sujeni; Diddo Adding Adove; Gilang Pranajasakti (Indragiri Research Center (ingreat), 2025)
This study aims to determine how much influence the analysis of the influence of capital structure and corporate income tax payable has on earnings management in manufacturing companies listed on the Indonesia Stock Exchange. The data analysis method is a type of secondary data with a research sample of 54 companies. The data analysis method used is secondary data type analysis. Using SPSS 23 software in data processing. Data collection techniques use documentation techniques. The results of the study obtained based on the partial test (t test) were obtained: There is an influence of capital structure on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024, There is no influence of corporate income tax payable on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024, There is an influence of capital structure and corporate income tax payable on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the period 2022-2024.